PENERAPAN INKUIRI TERSTRUKTUR BERBASIS PERMASALAHAN LINGKUNGAN DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA PADA MATERI PENCEMARAN UDARA DAN AIR - Rahayuningsih, Widayati; Qosyim, Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the improvement of students' critical thinking skills, the implementation of structured inquiry learning, and students' responses after participating in structured inquiry learning on air and water pollution material. This research uses a pre-experimental method with a one group pretest-posttest design. The subjects were 33 students of class VII-G at SMP Negeri 3 Sidoarjo for the 2025/2026 academic year. Data were collected through critical thinking skills tests (pretest-posttest), observation sheets of learning implementation, and student response questionnaires. Data analysis used normality test, paired sample t-test, and N-Gain analysis. The results showed: (1) there was a significant increase in students' critical thinking skills, with an average pretest score of 35.48 increasing to 76.52 on the posttest (significance value 0.000 < 0.05); N-Gain analysis showed 73% of students in the moderate category and 27% in the high category; (2) the implementation of structured inquiry learning for two meetings was in the very good category with a mode score of 4; (3) student responses to learning showed very positive results with scores of 88% for learning quality, 88% for the inquiry process, 89% for critical thinking skills, and 87% for attitudes and interest in learning. These findings indicate that the implementation of the structured inquiry model on air and water pollution material is effective in improving students' critical thinking skills.Keywords: Structured Inquiry, Critical Thinking Skills, Air and Water Pollution